2013
DOI: 10.1109/tmm.2012.2225030
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the External Links of Video Sharing Sites: Measurement and Analysis

Abstract: Recently, many video sharing sites provide external links so that their video or audio contents can be embedded into external web sites. For example, users can copy the embedded URLs of the videos of YouTube and post on their own blogs. Clearly, the purpose of such functionality is to increase the distribution of the videos and the associated advertisement. In this paper, we provide a comprehensive measurement study and analysis on these external links. With the traces collected from two major VOD sites, YouTu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…For example, Cha et al [3] studied the popularity distribution and evolution for UGC content by collecting data traces from two large UGC video systems. Li et al [4] [14] showed that external links of video sharing sites can significantly affect video popularity and its dynamics. Some works also leverage the measurement of popularity dynamics to study more realistic schemes.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Cha et al [3] studied the popularity distribution and evolution for UGC content by collecting data traces from two large UGC video systems. Li et al [4] [14] showed that external links of video sharing sites can significantly affect video popularity and its dynamics. Some works also leverage the measurement of popularity dynamics to study more realistic schemes.…”
Section: Related Workmentioning
confidence: 99%
“…Then, researches on YouTube datasets have been a hot topic, which includes mining latent information of users [7][8][9] [10]. Most of previous work only uses video metadata, including links [10], geographic location [9], view count [7] and so on. However, in this work, besides video-accompanied metadata, visual content is also used for constructing social networks.…”
Section: Topic Participants In Internet Videosmentioning
confidence: 99%
“…In a microblogging system, users can create and maintain social connections among each other, as well as subscribe to contents shared by others from external content sharing system, as followers [1]. Among the variety of contents to exchange, links to videos on video sharing sites are a popular type -users from microblogging exchanges are constituting a large portion of viewers in YouTube-like video sharing sites [2]. Popularity patterns of such socialized videos have greatly changed as follows:…”
Section: Introductionmentioning
confidence: 99%
“…The potential benefits are two-fold: (1) a video sharing site typically has no information about how video views propagate among its users, while a view propagation model could enable more effective view prediction; (2) the exchanges of video links in a microblogging system typically happen earlier than the actually video views on a video sharing site, and the time lag between both events can allow more timely and proactive deployment of videos. Based on our preliminary findings of the connection between the popularity of a video and how the video is shared in a microblogging system [8], in this paper, we focus on employing video microblog propagation patterns to improve the deployment of video services.…”
Section: Introductionmentioning
confidence: 99%